THE EFFECT OF TAX INCENTIVES AND GOOD CORPORATE GOVERNANCE ON TAX AVOIDANCE - Fauziah, Risma Resti; Widiyati , Dian (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this research is to examine and analyze the effect of tax incentives and good corporate governance on tax Avoidance. Population in this research is a manufacturing company food and beverage sector listed in Indonesia Stock Exchange period 2016-2020. The sample of research by using purposive sampling method as 12 companies that meet in the criteria. The technique used to test the hypothesis in this study is panel data regression, with data processing using the E-views 10 program. The results show that tax incentives and good corporate governance simultaneously affect the tax avoidance. While partially the institutional ownership and audit quality variable has an effect on tax avoidance, tax incentives and independent commissioners have no effect on tax avoidance.